Distress and Productivity Loss Associated with Uterine Fibroids: Results From a U.S. Survey [5D]. (May 2018) - Marsh, Erica E.; Al-Hendy, Ayman; Kappus, Dale; Galitsky, Alex; Kerolous, Majid; Stewart, Elizabeth A.
Abstract : INTRODUCTION: Uterine fibroids (UF) are highly prevalent among reproductive-age women with up to 50% of US women reporting symptoms that may be undiagnosed or untreated. The objective of this survey included understanding the impact of UF symptoms. METHODS: Female participants (≥18 years) were recruited via email from GfK KnowledgePanel®, a nationally representative panel of U.S. households, supplemented with opt-in consumer panels. The survey was 40-minutes long and used instruments such as the UFS-QoL and Aberdeen menorrhagia severity scale (AMSS). RESULTS: A total of 1, 443 women were considered eligible and included in the study. Of the diagnosed women without hysterectomy (n=871), 68% passed blood clots, and 32% used ≥6 forms of protection/day based on the AMSS. Based on the UFS-QoL Symptom Severity Subscale, 44% and 43% of diagnosed women reported fatigue and heavy bleeding, respectively, as causing a 'great deal/very great deal' of distress. One-fifth of working women missed ≥8 work-hours monthly (21% full-time, 23% part-time workers). Of women who were undiagnosed but had UF-like symptoms ('at-risk'; n=300), only 49% were aware of UF. Approximately 84% passed blood clots, and 55% used ≥6 forms of protection/day. Of the at-risk women, 83% and 78% reported fatigue and heavy bleeding, respectively, as causing a 'great deal/very great deal' of distress. Overall, 22% full-time and 45% part-time workers missed ≥8 work-hours monthly. CONCLUSION: Women with UF experience distress and impaired work productivity. A substantial number of women may be undiagnosed with significant symptoms, underscoring the need for improved awareness and management of UF.